Application of Marketing Mix in Islamic Perspective at 212 Mart - Asrizal Efendy Nasution; Linzzy Pratami Putri; Rini Astuti Astuti (Li Falah: Jurnal Studi Ekonomi dan Bisnis Islam, 2022)
The shopping centres built today all lead to modern focus centres with conventional concepts that provide excellent service and offer convenience and comfort to create customer loyalty. A new business model with a sharia concept has emerged in recent years, namely 212 Mart. 212 Mart has a sharia concept and has succeeded in attracting public interest because it is the only franchise with a sharia concept in Indonesia. However, the people's expectation of switching to 212 Mart was not followed by the people's loyalty to always shop at 212 Mart. Many factors influence customer loyalty, one of which can be seen in the marketing mix. It is necessary to evaluate the marketing mix carried out at 212 Mart, which consists of product quality, pricing, place or distribution, and promotions. Applying a marketing mix by Islamic law can be a factor in creating customer loyalty. The quality of halal products, whether available, distributed or where sellers and buyers meet who have a long-distance from one store to another, rarely carried out promotions, and pricing under Islamic law can affect customer loyalty for 212 marts.